1999
DOI: 10.1006/jmaa.1998.6159
|View full text |Cite
|
Sign up to set email alerts
|

Interval Criteria for Oscillation of Second-Order Linear Ordinary Differential Equations

Abstract: New oscillation criteria are established for the equation py q qy s 0 that are different from most known ones in the sense that they are based on the informaw . tion only on a sequence of subintervals of t , ϱ , rather than on the whole 0 half-line. Our results are more natural according to the Sturm Separation Theorem and sharper than some previous results, and can be applied to extreme cases such ϱ Ž . as H q t dt s yϱ. ᮊ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 10 publications
8
102
1
Order By: Relevance
“…First results of this type were obtained by El-Sayed [3] and later by Huang [7], Kong [9], Li and Agarwal [10], Nasr [12], Sun [16,17], Tiryaki and Zafer [18], and Zheng [22]. These criteria, called interval oscillation theorems, are especially efficient in situations when, for instance, +∞ q(s)ds = −∞, and many advanced oscillation results based on the standard integral averaging technique fail to apply.…”
Section: Introductionmentioning
confidence: 99%
“…First results of this type were obtained by El-Sayed [3] and later by Huang [7], Kong [9], Li and Agarwal [10], Nasr [12], Sun [16,17], Tiryaki and Zafer [18], and Zheng [22]. These criteria, called interval oscillation theorems, are especially efficient in situations when, for instance, +∞ q(s)ds = −∞, and many advanced oscillation results based on the standard integral averaging technique fail to apply.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the scalar equation (2), as implied by the Sturm Separation Theorem, oscillation is essentially an interval property, i.e., if there exists a sequence of subintervals [a i , b i ] of [t 0 , ∞), a i → ∞, such that for each i, there exists a solution of (2) which has at least two zeros in [a i , b i ], then every solution of (2) is oscillatory no matter how "bad" the scalar equation (2)(or (3)) is on the remaining parts of [t 0 , ∞). Based on these facts, Kong [7] gives interval type criteria for the oscillation of system (2), which are extensions of those for scalar equations obtained by Kong [11]. Meanwhile, the oscillation of a system with damping has drawn less attention, Zheng [13] gave oscillation criteria for system (1), which generalize Theorem A.…”
Section: Zhaowen Zheng and Jingzhao Liumentioning
confidence: 99%
“…It has been shown that many real world problems can be modelled, in particular, by half linear differential equations which can be regarded as a natural generalization of linear differential equations [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. A considerable amount of research has also been done on quasi-linear [15][16][17][18] and nonlinear second order differential equations [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%